(untitled) (Geo-Eco-Marina, 2020)
Since the resume in 2005 of the systematic geophysical and geo-ecological investigation of the Romanian offshore, over 13,400 km of gravity lines and over 48,000 km of magnetic lines have been acquired on the entire surface of the Romanian maritime space and over most of the Bulgarian one. Based on this data numerous maps of the gravity and magnetic anomalies, at scales ranging from regional to the highest detail, have been compiled. If prior to 1990, marine gravity and magnetic researches were exclusively used for the study of the Romanian continental shelf deep geological structure and for the assessment of its hydrocarbon potential, the latter researches has expanded the range of topics addressed: deciphering of also near surface structures, marine site characterization, geo-archaeology, environmental geophysics, detection of submerged objects, maritime space security. Mainly during the last years, an increasing involvement of marine magnetometry in projects dedicated to the study of the submarine cultural heritage and to enhancement of maritime space safety is noticed. The present results and findings due to marine magnetometry go far beyond all initial expectations.